Uninterrupted optical resolution of identical point scatterers undergoing nanometric changes in distance - Thomas A. Hensel; Ole L. Schwarz; Tim Karrasch; Kerstin Göpfrich; Stefan W. Hell (Proceedings of the National Academy of Sciences, 2026)
In established superresolution fluorescence microscopy or nanoscopy, resolving identical fluorescent molecules at subdiffraction distances requires the molecules to emit sequentially so that they briefly become discernible from their neighbors one after another. Simultaneous tracking of multiple fluorophores that are only a few nanometers apart is thus conceptually and practically impossible. We have recently shown that probing a subdiffraction region with an excitation beam featuring an intensity zero, i.e., MINFLUX superresolution, localizes and resolves closely packed identical fluorophores without interruption. Here, we provide a conceptual framework for resolving and tracking constantly emitting identical fluorophores—more generally, point scatterers—that undergo random changes in position. In particular, we show that the detection rates available in fluorescence microscopy are sufficient to track sub-10 nm distance changes within micro- to milliseconds. By using a DNA origami construct with a fixed and a movable fluorophore as a proxy, we provide a proof-of-concept that thermally driven conformational changes of macromolecules are continuously detectable with visible light. Conformational changes of the DNA nanostructure leading to random jumps in distance of about 10 nm between two labels are registered within ~1 ms. Our work paves the way toward superresolving complex conformational transitions of individual biomolecules with focused light.